"Caribou was the reason, and everything else happened after": Effects of caribou declines on Inuit in Labrador, Canada. (May 2021) - Borish, David; Cunsolo, Ashlee; Snook, Jamie; Shiwak, Inez; Wood, Michele; HERD Caribou Project Steering Committee; Mauro, Ian; Dewey, Cate; Harper, Sherilee L.
Graphical abstract: Highlights: Visual method reveals new insights into caribou decline effects on Inuit wellbeing. Complex alterations to Inuit identity result from caribou-related change. Caribou-related changes leading to losses of Inuit cultural knowledge and meaning. Ongoing adaptive strategies to replace caribou are insufficient for Inuit wellbeing. Abstract: For many Indigenous Peoples in the Circumpolar North, cultural engagement and continuity across generations is directly related to relationships between and among people, animals, and landscapes. However, minimal research outlines the emotional responses and disruptions to culture and identity that are driven by ecological change, and the subsequent cultural dimensions of coping and adapting to this uncertainty. Through a case study that explores how caribou population declines and a caribou hunting ban are impacting Inuit in the Nunatsiavut and NunatuKavut regions of Labrador, Canada, this article examines the critical interplay between cultural continuity and adaptive capacity for responding to ecological uncertainty. More specifically, this study: 1) described the central role that caribou play for Inuit emotional wellness, identity, and cultural continuity; 2) explored how the rapid declines of caribou in Labrador are affecting Inuit emotional wellness, identity, and cultural continuity; and 3) characterized the ways in which Inuit are adapting to these emotio-social, cultural, and ecological changes. Drawing from an Inuit-led, multi-year, multi-media qualitative and visual media research program, data from video interviews (n = 84: Nunatsiavut region: n = 54; NunatuKavut region: n = 30) were analyzed using a video-based qualitative analysis, constant-comparative methods, and inductive qualitative approach. Results indicated that caribou are a foundational element for Inuit emotional wellness, identity, and cultural continuity. The changes in caribou populations are resulting in complex emotional responses, losses to cultural meaning and knowledge, and alterations to Inuit identities. The impacts on emotions, identity, and cultural continuity related to Inuit-caribou relations at an individual and collective level reflect the interconnections between cultural continuity and adaptive capacity that underlie the loss of this culturally important species. Though this research focuses on two Inuit groups and caribou in Labrador, the insights from these lived experiences highlight the ongoing cultural and identity consequences associated with species declines occurring globally.